Plant-Based Vaccines Against COVID-19 for Massive Vaccination in Africa - El Jaddaoui, Islam; Al Idrissi, Najib; Hamdi, Salsabil; Wakrim, Lahcen; Nejjari, Chakib; Amzazi, Saaïd; Elouahabi, Abdelatif; Bakri, Youssef; Ghazal, Hassan (Frontiers in Drug Delivery, 2022)
During the unprecedented COVID-19 pandemic, the primary goal of many countries has been to achieve herd immunity through the organization of massive vaccination campaigns. Nevertheless, developing countries, including Africans, have been facing limited vaccine supply. Conventional inactivated or subunit vaccines are widely used across the world; however, their production is costly and could be limited by the supply chain during a pandemic such as COVID-19. Genetic vaccines, such as mRNA- or adenovirus-based vaccines, have been developed as alternatives but are still costly and require low-temperature storage. The plant-based vaccine concept has attracted increasing attention in recent years due to its potential advantages, such as low cost, high production volume, and thermostability. In this review, we propose plant-based vaccines as an attractive alternative for massive and rapid vaccination protocols against COVID-19 in African countries by exploiting local crops. In addition, we discuss the mechanisms of action, required standards, benefits, challenges, and prospects for the application of this novel biotechnological tool in the African continent.